2008
DOI: 10.1073/pnas.0710535105
|View full text |Cite
|
Sign up to set email alerts
|

Both ovarian hormones estrogen and progesterone are necessary for hormonal mammary carcinogenesis in ovariectomized ACI rats

Abstract: August-Copenhagen-Irish (ACI) rats are unique in that the ovaryintact females develop high incidence of mammary cancers induced solely by hormones upon prolonged exposure to high levels of estrogen alone. Studies have also shown that such prolonged exposure to high-dose estrogen results in human-like aneuploid mammary cancers in ovary-intact ACI rats. To determine the role of progesterone in mammary carcinogenesis, six-week-old intact and ovariectomized ACI rats were continuously exposed to low-and high-dose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
(66 reference statements)
3
26
0
Order By: Relevance
“…DMBA is a commonly used breast targeted carcinogen in rodents by intragastric administration [24,38], and it seemed to work somewhat in our tree shrew groups, as DMBA induced one intraductal papilloma in subject #30. Other evidence has suggested that progestin increased the risk of breast cancer in women [39,40], and progesterone and its derivative MPA have been shown to be sufficient in including mammary carcinomas among rodents [41][42][43], cats and dogs [44]. Furthermore, MPA has also been shown to accelerate DMBA-induced breast tumour development in both rats [45] and mice [15,24,46].…”
Section: Discussionmentioning
confidence: 99%
“…DMBA is a commonly used breast targeted carcinogen in rodents by intragastric administration [24,38], and it seemed to work somewhat in our tree shrew groups, as DMBA induced one intraductal papilloma in subject #30. Other evidence has suggested that progestin increased the risk of breast cancer in women [39,40], and progesterone and its derivative MPA have been shown to be sufficient in including mammary carcinomas among rodents [41][42][43], cats and dogs [44]. Furthermore, MPA has also been shown to accelerate DMBA-induced breast tumour development in both rats [45] and mice [15,24,46].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that exposure to increased levels of these hormones increases the risk for breast cancer [1][2][3][4][5]. However, relatively little is known about how E2 and PRL interact at the level of mammary epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Akin to the human scenario, high levels of circulating E 2 causes mammary tumors in these rats (14,15). Both progesterone and estradiol are required for the development of tumors (16). E 2 causes DNA and epigenetic damage in the mammary (17,18), and blocking of E 2 metabolizing enzymes or estrogen receptors abrogate the tumorigenesis (19).…”
Section: Introductionmentioning
confidence: 99%